ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE PADA ANTOLOGI PUISI SELAMAT MENUNAIKAN IBADAH PUISI KARYA JOKO PINURBO - Najwa Chautsar Adhelia; Heru Prasetyo; Munaris Munaris (FKIP Universitas Lampung, 2025)
Poetry is a type of literary work that conveys ideas and feelings of the poet with language as a beautiful medium bound by structure, rhythm, and rhyme. This research aims to conduct a semiotic study of Ferdinand de Saussure on the poetry anthology